An Aesthetic Visualization of Ritual Ordering among the Yoruba Drummer: A Medium of Life Celebration - Olusegun Adebolu Oladosu (Yoruba Studies Review, 2021)
The gatherings among Yoruba people depicting religion, social or political values are usually staged with drumming. At the center of this art are the professional drummers with the cult identity of àyàn. The display, ordering and aesthetic of drumming are usually often come with some rituals during passages of life which are frequently unknown to the non-initiates. The study underscores the significant of ritual that are connected to birth, puberty, middle stage and death which are very important to life stages among the Yoruba people. It highlights the role of ritual rites in the profession of drumming in a selected town in Yoruba land. The paper use in-depth interview, participant observation, archival materials and ethnographic methods to generate data needed for its analysis. Tis paper through phenomenological analysis will process the data collected.